Characterizing of Nano Activated Bio-Carbon of Sago Waste as a Homogeneous Combustion Catalyst - Hendry Y. Nanlohy; Helen Riupassa; Muji Setiyo (Universitas Muhammadiyah Magelang, 2024)
Alternative fuels were developed by blending crude coconut oil and bio-carbon nanoparticles. Bio-carbon, derived from sago waste via pyrolysis and ground using a ball mill, underwent FTIR testing to assess its energy absorption capabilities. SEM analysis was conducted to examine the surface morphology of bio-catalyst with and without crude coconut oil. The findings indicate that incorporating bio-catalyst can enhance mechanical properties, facilitating rapid heat absorption, as evidenced by reduced flashpoint and viscosity. In addition, the results show an increase in fuel mass, broadening of molecular contacts, increased reactivity, and increased heat absorption for easier ignition. This phenomenon indicates that bio-carbon of sago waste have great potential for biofuel use as a homogeneous combustion catalyst.